LACTB suppresses melanoma progression by attenuating PP1A and YAP interaction. (28th May 2021) - Ma, Yawen; Wang, Lihua; He, Fanglin; Yang, Jie; Ding, Yi; Ge, Shengfang; Fan, Xianqun; Zhou, Yixiong; Xu, Xiaofang; Jia, Renbing
Abstract: Very limited progress has been made in the management of advanced melanoma, especially melanoma of uveal origin. Lactamase β (LACTB) is a novel tumor suppressor; however, its biological function in melanoma remains unknown. Herein we demonstrated markedly lower LACTB expression levels in melanoma tissues and cell lines. Overexpression of LACTB suppressed the proliferation, migration and invasion of melanoma cells in vitro . Mechanistically, LACTB inhibited the activity of yes-associated protein (YAP). We showed that the level of phospho-YAP (Serine 127) was increased upon LACTB overexpression, which prevented the translocation of YAP to the nucleus. Further, LACTB could directly bind to PP1A and attenuate the interaction between PP1A and YAP, resulting in decreased YAP dephosphorylation and inactivation in a LATS1-independent manner. Additionally, transfection of phosphorylation-defective YAP mutants reversed LACTB-induced tumor suppression. Upstream, we demonstrated that SOX10 binds to the LACTB promoter and negatively regulates its transcription. Overexpression of LACTB also suppressed the tumorigenicity and lung metastasis of MUM2B uveal melanoma cells in vivo . Taken together, our findings indicate a novel SOX10/LACTB/PP1A signaling cascade that renders YAP inactive and modulates melanoma progression, offering a new therapeutic target for melanoma treatment. Highlights: LACTB suppresses the malignant phenotypes of melanoma both in vitro and in vivo. LACTB inhibits YAP activity by increasing its phosphorylation at S127. LACTB attenuates the interaction of PP1A with YAP, leading to decreased dephosphorylation of YAP. SOX10 binds to the promoter of LACTB and negatively regulates its expression.